Sistem Informasi Pengenalan Tanaman Menggunakan QR Code Scanner - Firmansyah Ibrahim; Zulkarnaim Masyhur; Khaerunsituncu Khaerunsituncu (Journal Software, Hardware and Information Technology, 2021)
There are many different kinds of plants that can be found anywhere, but we don't know precisely what types and uses they are, so it's good for us to understand these plants. The purpose of this research is to make it easier to find out about plants by designing and building an information system about plant qualifications using QR Code technology combined with the Website application. This type of research used in this research is a qualitative method. Qualitative methods are research methods that are descriptive and tend to use analysis. Process and meaning (subject perspective) are emphasized more in qualitative methods. While the data collection methods used were observation, interviews and literature study. The application planning method used is a waterfall. In contrast, the testing technique used by the author is Black Box testing. The results of this research are in the form of a web-based plant recognition information system to make it easier for administrators to provide information and make it easier for visitors to get plant information. Based on the test results, it can be concluded that this system is running according to the common objectives.